A review of mercury exposure among artisanal small-scale gold miners in developing countries - Kristensen, Anders Kasper Bruun; Thomsen, Jane Frølund; Mikkelsen, Sigurd (International archives of occupational and environmental health, 2014)
Purpose Extraction of gold using mercury has been a way out of poverty for millions of people in developing countries. Artisanal small-scale gold mining (ASGM) has expanded during the last decades and is often carried out under primitive conditions. Thus, workers in this industry may be exposed to high levels of mercury and suffer from toxic effects from mercury exposure. The objective of this review was to provide an outline of the studies available on elemental mercury exposure among artisanal small-scale gold miners. Methods Searching the PubMed and Embase databases, 26 studies with a total of 3,005 exposed subjects and 442 controls across 14 different developing countries were found. Urine mercury levels were used as biomarkers of exposure. Results In general, the urine mercury levels were elevated and a considerable proportion of workers had urine mercury levels above existing guidelines. Exposed subjects were stratified into residents, miners, millers, smelters, and refiners, who by work task content were expected to be increasingly exposed to mercury. This group order did show a clear trend of increasing mercury levels. Mercury levels differed substantially between studies. Possible explanations include dissimilarities in gold extraction methods, use of protective devices, and selection of participants. Conclusions This review provides evidence that artisanal gold miners and residents of the mining sites are exposed to mercury vapour to an extent where acute and long-term toxic effects of mercury are likely. Interventions aimed at reducing exposure and emission of mercury from ASGM are needed.